Change & continuity in the value-priorities of school-leavers in Rundu (Namibia): a comparative study of hybridization and its development implications - Field, Michael (Department of Sociology, 2018)
In Southern Africa, burgeoning intercultural contact results in the emergence of (bicultural) sociocultural contexts which emphasize African traditional and Western industrial values to different degrees. In transitioning between these contexts, Southern Africans may experience feelings of dissonance which potentially threaten identity. In managing these transitions, individuals arguably employ various hybridization strategies in order to navigate socio-cultural contexts whilst maintaining a coherent sense of self. Though part of a broader Southern African study initiated by Cumpsty in 1998, this dissertation represents a stand-alone inquiry into how the value-priorities of school-leaving respondents in Rundu, northern Namibia, have changed or stayed the same between 1998 and 2017. What is more, it seeks to ascertain if/how these respondents have hybridized their value-systems confronted with increasingly bicultural experiences. Cumpsty's quantitative instrument for measuring values was administered to the entire school-leaving cohort in two schools in Rundu in 1998 and in 2017. This data was comparatively analyzed using descriptive and inferential statistics in order to measure the extent to which change/continuity had occurred over the nearly 20 year period. Profiles were generated from the two sets of quantitative data, which revealed how respondents hybridized African traditional and Western industrial values, and the results were analyzed comparatively. This dissertation's central finding has been an unexpected pattern of general continuity in the value-priorities of respondents between 1998 and 2017, which is also demonstrated in the patterns found in the dominant profiles. These results indicate the use of distinct strategies which allow respondents to integrate African traditional and Western industrial values into hybrid value-systems - which in turn allow them to navigate bicultural experiences whilst maintaining a coherent sense of identity - and therefore repudiates the notion of globalisation resulting in increasing socio-cultural uniformity. This finding indicates that if the definition of development is broadened to encompass the satisfaction of fundamental human needs, then an account of identity is crucial, which in turn renders an account of values indispensable to the development debate in Southern Africa. Lastly, this dissertation uses Cumpsty's instrument, which is fundamentally flawed, and ends with a critique of the instrument.